Teknik Audit Berbantuan Komputer sebagai Pemoderasi Integritas dan Kompetensi Auditor terhadap Kualitas Audit - Putu Wahyu Inspirawan; Putu Purnama Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the effect of auditor integrity and auditor competence on audit quality, with Computer-Assisted Audit Techniques (CAATs) as a moderating variable. The study is grounded in attribution theory, which explains that auditor behavior is influenced by internal factors such as integrity and competence, as well as external factors such as the use of audit technology. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to auditors working at Public Accounting Firms (PAFs) in Bali Province. The sampling technique used was purposive sampling, and data analysis was conducted using Partial Least Square (PLS) with a moderated regression model. The results indicate that auditor integrity and auditor competence have a positive and significant effect on audit quality. Furthermore, CAATs have a significant effect on audit quality and are proven to moderate the relationship between auditor integrity and audit quality, as well as between auditor competence and audit quality. These findings suggest that the implementation of CAATs strengthens the role of auditor integrity and competence in producing high-quality audits. This study provides practical implications for Public Accounting Firms to enhance audit quality by strengthening auditor integrity, improving auditor competence, and optimizing the use of computer-assisted audit techniques.